Functionalization of N-arylglycine esters: electrocatalytic access to C–C bonds mediated by n-Bu4NI - Luo, Mi-Hai; Jiang, Yang-Ye; Xu, Kun; Liu, Yong-Guo; Sun, Bao-Guo; Zeng, Cheng-Chu (Beilstein Journal of Organic Chemistry, 2018)
An efficient electrocatalytic functionalization of N-arylglycine esters is reported. The protocol proceeds in an undivided cell under constant current conditions employing the simple, cheap and readily available n-Bu4NI as the mediator. In addition, it is demonstrated that the mediated process is superior to the direct electrochemical functionalization.
Keywords: C–C formation; electrochemical oxidative functionalization; n-Bu4NI; redox catalyst

(untitled) - Girard, S. A.; Knauber, T.; Li, C.-J. (Angew. Chem., Int. Ed., 2014)

(untitled) - Scheuermann, C. J. (Chem. – Asian J., 2010)

(untitled) - Ritleng, V.; Sirlin, C.; Pfeffer, M. (Chem. Rev., 2002)

(untitled) - Xu, H.-J.; Lu, Y.; Farmer, M. E.; Wang, H.-W.; Zhao, D.; Kang, Y.-S.; Sun, W.-Y.; Yu, J.-Q. (J. Am. Chem. Soc., 2017)

(untitled) - Jiang, H.; He, J.; Liu, T.; Yu, J.-Q. (J. Am. Chem. Soc., 2016)

(untitled) - Chatani, N.; Asaumi, T.; Yorimitsu, S.; Ikeda, T.; Kakiuchi, F.; Murai, S. (J. Am. Chem. Soc., 2001)

(untitled) - Li, Z.; Li, C.-J. (J. Am. Chem. Soc., 2005)

(untitled) - Condie, A. G.; González-Gómez, J. C.; Stephenson, C. R. J. (J. Am. Chem. Soc., 2010)

(untitled) - Freeman, D. B.; Furst, L.; Condie, A. G.; Stephenson, C. R. J. (Org. Lett., 2012)

(untitled) - Hari, D. P.; König, B. (Org. Lett., 2011)

Principles of proteomics - Twyman, R. M. (BIOS Scientific Publishers, 2004)

(untitled) - Zhao, L.; Li, C.-J. (Angew. Chem., Int. Ed., 2008)

(untitled) - Li, C.-J. (Acc. Chem. Res., 2009)

(untitled) - Xie, J.; Huang, Z.-Z. (Angew. Chem., Int. Ed., 2010)

(untitled) - Zhu, Z.-Q.; Bai, P.; Huang, Z.-Z. (Org. Lett., 2014)

(untitled) - Salman, M.; Zhu, Z.-Q.; Huang, Z.-Z. (Org. Lett., 2016)

(untitled) - Huo, C.; Wang, C.; Wu, M.; Jia, X.; Xie, H.; Yuan, Y. (Adv. Synth. Catal., 2014)

(untitled) - Gao, X.-W.; Meng, Q.-Y.; Xiang, M.; Chen, B.; Feng, K.; Tung, C.-H.; Wu, L.-Z. (Adv. Synth. Catal., 2013)

(untitled) - Yang, X.; Li, L.; Li, Y.; Zhang, Y. (J. Org. Chem., 2016)

(untitled) - Sperry, J. B.; Wright, D. L. (Chem. Soc. Rev., 2006)

(untitled) - Francke, R.; Little, R. D. (Chem. Soc. Rev., 2014)

(untitled) - Horn, E. J.; Rosen, B. R.; Baran, P. S. (ACS Cent. Sci., 2016)

(untitled) - Yang, Q.-L.; Li, Y.-Q.; Ma, C.; Fang, P.; Zhang, X.-J.; Mei, T.-S. (J. Am. Chem. Soc., 2017)

(untitled) - Schäfer, H. J. (Angew. Chem., Int. Ed., 2017)

(untitled) - Zhao, H.-B.; Hou, Z.-W.; Liu, Z.-J.; Zhou, Z.-F.; Song, J.; Xu, H.-C. (Angew. Chem., Int. Ed., 2017)

(untitled) - Wang, P.; Tang, S.; Huang, P.; Lei, A. (Angew. Chem., Int. Ed., 2017)

(untitled) - Jiang, Y.; Xu, K.; Zeng, C. (Chem. Rev., 2017)

(untitled) - Li, W.-C.; Zeng, C.-C.; Hu, L.-M.; Tian, H.-Y.; Little, R. D. (Adv. Synth. Catal., 2013)

(untitled) - Chen, J.; Yan, W.-Q.; Lam, C. M.; Zeng, C.-C.; Hu, L.-M.; Little, R. D. (Org. Lett., 2015)

(untitled) - Liang, S.; Zeng, C.-C.; Luo, X.-G.; Ren, F.-z.; Tian, H.-Y.; Sun, B.-G.; Little, R. D. (Green Chem., 2016)

(untitled) - Kang, L.-S.; Luo, M.-H.; Lam, C. M.; Hu, L.-M.; Little, R. D.; Zeng, C.-C. (Green Chem., 2016)

(untitled) - Ni, M.; Zhang, Y.; Gong, T.; Feng, B. (Adv. Synth. Catal., 2017)

(untitled) - Gandeepan, P.; Rajamalli, P.; Cheng, C.-H. (Asian J. Org. Chem., 2014)

(untitled) - Xie, Z.; Jia, J.; Liu, X.; Liu, L. (Adv. Synth. Catal., 2016)

(untitled) - Liu, J.; Wang, Y.; Yu, L.; Huo, C.; Wang, X.; Jia, X. (Adv. Synth. Catal., 2014)

(untitled) - Rohlmann, R.; Stopka, T.; Richter, H.; Garcı́a Mancheño, O. (J. Org. Chem., 2013)